Owner’s attitudes, perception and satisfaction toward spaying and neutering in cats - Amin, F; Poddar, S; Paul, T; Das, B C; Sutradhar, B C; Dey, T (Bangladesh Veterinarian, 2024)
Abstract not available Bang. vet. 2024. Vol. 41, No. 1 – 2, 23 – 24